A valid priacanthid species, Pristigenys refulgens (Valenciennes 1862), and a redescription of P. niphonia (Cuvier in Cuvier & Valenciennes 1829) in the Indo-West Pacific (Perciformes: Priacanthidae) - Iwatsuki, Yukio; Matsuda, Tsuyoshi; Starnes, Wayne C.; Nakabo, Tetsuji; Yoshino, Tetsuo (Zootaxa, 2012)
Pristigenys refulgens (Valenciennes 1862) is herein redescribed as a valid species although it has long been synonymizedunder P. niphonia (Cuvier in Cuvier & Valenciennes 1829). Pristigenys refulgens differs from the latter in having lowergill raker counts, fewer lateral-line scales and spinules on body scales, shape of the caudal fin, and in fin and body color-ation. Pristigenys refulgens is currently known from the Indian and western Pacific oceans from South Africa and the RedSea eastward to Indonesia and Japan, while P. niphonia is confined to the western Pacific from Japan to northern Australia,and possibly eastward to Samoa. A neotype for Pristigenys niphonia is herein designated. A key is provided for the IndoWest Pacific Pristigenys species.